Study of Integrated Ticketing Systems in Banyuwangi Tourism Destinations - Febrian, Ayu Wanda; Mukti, Masetya; Handoko, Rudi Tri; Perdana, Muhamad Ari (KnE Social Sciences, 2024)
The absence of an integrated system between tourist attractions, accessibility points, and accommodations is affecting the variation in tourist visit data received by each tourism-related agency in Banyuwangi regency. This research aims to examine the most effective and efficient integrated ticketing system that Banyuwangi Regency Government can immediately adopt, to collect and compile accurate tourist visit data from the tourist attractions, accessibility, and accommodation in Banyuwangi. The design of this research used descriptive qualitative with a meta-analysis approach. The result of this research shows that the Banyuwangi Regency Government has attempted to create mobile applications to realize tourism marketing programs and facilitate data collection of tourist visits, namely the “Banyuwangi Tourism” and “Banyuwangi E-Ticketing” applications. To minimize data collection on the number of repeated tourist visits at each tourist attraction visited, these two applications can be integrated and developed further by implementing integrated payment via QR Code where the Banyuwangi Tourism application can also function as a payment medium to scan barcodes provided in the management of tourist attractions through the “E-Ticketing Banyuwangi” application to fulfill the purpose of integrated data. Keywords: integrated system, tourism data, QR code, ticket system, tourism destination